2019
DOI: 10.1088/2058-6272/ab4c6a
|View full text |Cite
|
Sign up to set email alerts
|

Spectral characteristic of laser-induced plasma in soil

Abstract: The spectral characteristic of laser-induced plasma in soil was studied in this work, laser-induced breakdown spectroscopy was used to analyze the spectral characteristic of plasma under the condition of different time delays and irradiances. Moreover, the time evolution characteristics of plasma temperature and electron density were discussed. Within the time delay range of 0-5 μs, the spectral intensity of the characteristic lines of Si I: 288.158 nm, Ti I: 336.126 nm, Al I: 394.400 nm and Fe I: 438.354 nm o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…A method for the measurement of non-metallic elements in herbal teas used 159 O 2 and H 2 sequentially as reaction gases. First, O 2 was introduced to the cell and Br, I, P and S measured as their oxide ions; then H 2 was introduced and Cl measured as H 2 35 Cl + and Si as 28 Improvements in the LIBS analysis of soil were achieved through study and optimisation of the laser energy, 165,166 pressure, 167 lens-to-sample distance 166 and time delay between irradiation and signal acquisition. [165][166][167] Application of a magnetic eld perpendicular to the plasma increased 168,169 plasma temperature and hence analyte emission intensities and thereby lowered LODs.…”
Section: Instrumental Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A method for the measurement of non-metallic elements in herbal teas used 159 O 2 and H 2 sequentially as reaction gases. First, O 2 was introduced to the cell and Br, I, P and S measured as their oxide ions; then H 2 was introduced and Cl measured as H 2 35 Cl + and Si as 28 Improvements in the LIBS analysis of soil were achieved through study and optimisation of the laser energy, 165,166 pressure, 167 lens-to-sample distance 166 and time delay between irradiation and signal acquisition. [165][166][167] Application of a magnetic eld perpendicular to the plasma increased 168,169 plasma temperature and hence analyte emission intensities and thereby lowered LODs.…”
Section: Instrumental Analysismentioning
confidence: 99%
“…Improvements in the LIBS analysis of soil were achieved through study and optimisation of the laser energy, 165,166 pressure, 167 lens-to-sample distance 166 and time delay between irradiation and signal acquisition. 165–167 Application of a magnetic field perpendicular to the plasma increased 168,169 plasma temperature and hence analyte emission intensities and thereby lowered LODs. Spatial confinement of the plasma within a cylindrical cavity achieved 170 the same result.…”
Section: Analysis Of Soils Plants and Related Materialsmentioning
confidence: 99%
“…Liu et al [10] studied the effect of excitation voltage on the separation flow under steady plasma excitation using this model. Yu et al [11] applied numerical simulations to study the effect of unsteady excitation and plasma excitation voltage on the separation of the same hump model.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [17] employed it to study the flow structures of the boundary layer in a flat plate induced by a plasma actuator. Yu et al [11] used the linear body approach and found that the vortex pairs, which are reduced by a plasma, would enhance the energy exchanged between the near wall region and the free stream. In the present work, the phenomenological body force approach proposed by Shyy et al [12] will be adopted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation